The Impact of Computer Assisted Language Learning (CALL) Technology on Indonesian Learners' Speaking Skills - Muhammad Chairil Imran; Khaliq Bashar; Budiarti Putri Uleng; Nina Ariani; Sukmawati; Suharti Siradjuddin; Sujarwo; Irman (CV. Eureka Murakabi Abadi, 2022)
The use of technology in learning English-speaking skills has grown rapidly. One such technology is the computer-aided learning media. The use of computer media in the field of education has many advantages as they are easier to access, disseminate and store. The aim of present study is to investigate the impact of computer assisted language learning (CALL) technology on Indonesian learners' speaking skills. This study applied quantitative research. The results of study found that the use of information technology in learning is marked by the interaction between students and materials through internet technology, the existence of programmed teaching, and flexibility in the process. learning both in terms of time and place. It can be concluded that it is very possible for us to be easily literate through various media, with this we can improve the quality of speaking.